A Mentorship Program for Academic Obstetrician Gynecologists that Improved Publication and Overall Confidence for Success - Nasab, Susan; Rushing, John S.; Segars, James H.; Evers, Emily; Handa, Victoria L.; Lawson, Shari; Miller, Colleen; Yenokyan, Gayane; Bienstock, Jessica; Satin, Andrew J. (Seminars in Reproductive Medicine, 2019)
This article aims to evaluate the impact of a mentorship program to enhance the training of clinical and research scientists in obstetrics and gynecology (OBGYN). A departmental course was developed for junior faculty and fellows based on their areas of interest. The research was IRB-approved. The curriculum consisted of monthly interactive workshops for an interdisciplinary group of trainees in OBGYN. Themes included research, education, and leadership in academic OBGYN. There was a strong emphasis on participatory exercises. Examples of curriculum topics included manuscript publication and review, grant writing, working with an IRB, promotion, and time management. Pre- and post-course questionnaires assessed participants' confidence in skills related to the course topics. Generalized linear models were used to assess changes in post-course response, using each question as the dependent variable and an indicator for post-course as the predictor variable. The control group was composed of junior faculty and fellows before the course was initiated. Outcome measures included the number and impact factor of published manuscripts. A Wilcoxon rank-sum test was used to assess outcome measures. Of the 118 attendees, 26 (22.0%) were junior faculty, 35 (29.66%) were clinical fellows, and 28 (23.7%) were research fellows, other research staff, or students. For each 3-year course series, an average of 20 participants completed the post-course surveys, of which 72% were clinical fellows, 22% were assistant professors, and 5% were instructors. The data revealed a statistically significant change in the participant's overall confidence in skills related to research, education, and leadership when comparing the cumulative results from the pre-to-post course surveys (p < 0.001). Specifically, participants noted improved confidence in their skills related to clinical and translation research (p < 0.001) and leadership and academic career advancement (p = 0.001). Additionally, junior faculty and clinical fellows who attended the course had a higher number of publications during the course period compared with controls (p = 0.003 and p = 0.008, respectively). This subspecialty-tailored, departmental training program was effective in increasing junior faculty and clinical fellows' confidence in skills related to career advancement and research and in the number of peer-reviewed publications.
Keywords: mentorship; leadership; OBGYN; fellowship